Cutaneous manifestation of Hodgkin’s disease - Hakim, Irshad (Journal of Postgraduate Medical Institute, 2011)
Hodgkin's disease is a malignant condition of lymphoid origin. It was first described by Dr. Thomas Hodgkin in 1832 when he was a lecturer of morbid anatomy and curator of the pathology museum at Guy's hospital London. It was Samual Wiks who proposed the name Hodgkin's disease in 1865. The etiology of this disease is still not clear but it is believed that in adults it may begin as a n inflammatory reaction to the infectious agent and in time course, may be converted to a neoplastic state.